Gambaran Pemenuhan Kebutuhan Spiritual pada Lanjut Usia - Ahmad Tegar Sunu Prakoso (STIKes Patria Husada Blitar, 2014)
With the growing elderly person, they will decline, especially in the physical abilities that can lead to a reducyion in the role of spiritual. The purpose of the research is to describe the spiritual needs of elderly with Immobility in UPT PSLU Blitar in Tulungagung. Method: The research design was description design. The population in this research is all elderly in UPT PSLU Blitar in Tulungagung as many as 80 people and great samples taken is as many as 29 people using total sampling technique. Data was collected by questionnaire. Result : The results of this research show that 55% elderly have a good spiritual, 14% quite, and 31% elderly have a less spiritual. Elderly are a vulnerable group of physical and mental deterioration caused various problems one spiritual. Discussion : Recommendations from the study are expected need for discipline in the religious guidance, especially in the elderly with immobility in UPT PSLU Blitar in Tulungagung.